Commit 6041c4e5 authored by Pavel Kus's avatar Pavel Kus

renaming further to w_comb

parent 12e38b75
......@@ -131,16 +131,16 @@
h_4_2 = hh(3,4)
h_4_1 = hh(4,4)
w(1:nq) = a_3_1(1:nq) * h_4_3 + a_4_1(1:nq)
w(1:nq) = a_2_1(1:nq) * h_4_2 + w(1:nq)
w(1:nq) = a_1_1(1:nq) * h_4_1 + w(1:nq)
w_comb(1:nq,4) = a_3_1(1:nq) * h_4_3 + a_4_1(1:nq)
w_comb(1:nq,4) = a_2_1(1:nq) * h_4_2 + w_comb(1:nq,4)
w_comb(1:nq,4) = a_1_1(1:nq) * h_4_1 + w_comb(1:nq,4)
z(1:nq) = a_2_1(1:nq) * h_3_2 + a_3_1(1:nq)
z(1:nq) = a_1_1(1:nq) * h_3_1 + z(1:nq)
w_comb(1:nq,3) = a_2_1(1:nq) * h_3_2 + a_3_1(1:nq)
w_comb(1:nq,3) = a_1_1(1:nq) * h_3_1 + w_comb(1:nq,3)
y(1:nq) = a_1_1(1:nq) * h_2_1 + a_2_1(1:nq)
w_comb(1:nq,2) = a_1_1(1:nq) * h_2_1 + a_2_1(1:nq)
x(1:nq) = a_1_1(1:nq)
w_comb(1:nq,1) = a_1_1(1:nq)
do i=5,nb
h1 = hh(i-3,1)
......@@ -148,29 +148,29 @@
h3 = hh(i-1,3)
h4 = hh(i ,4)
x(1:nq) = x(1:nq) + q(1:nq,i) * h1
y(1:nq) = y(1:nq) + q(1:nq,i) * h2
z(1:nq) = z(1:nq) + q(1:nq,i) * h3
w(1:nq) = w(1:nq) + q(1:nq,i) * h4
w_comb(1:nq,1) = w_comb(1:nq,1) + q(1:nq,i) * h1
w_comb(1:nq,2) = w_comb(1:nq,2) + q(1:nq,i) * h2
w_comb(1:nq,3) = w_comb(1:nq,3) + q(1:nq,i) * h3
w_comb(1:nq,4) = w_comb(1:nq,4) + q(1:nq,i) * h4
enddo
h1 = hh(nb-2,1)
h2 = hh(nb-1,2)
h3 = hh(nb ,3)
x(1:nq) = x(1:nq) + q(1:nq,nb+1) * h1
y(1:nq) = y(1:nq) + q(1:nq,nb+1) * h2
z(1:nq) = z(1:nq) + q(1:nq,nb+1) * h3
w_comb(1:nq,1) = w_comb(1:nq,1) + q(1:nq,nb+1) * h1
w_comb(1:nq,2) = w_comb(1:nq,2) + q(1:nq,nb+1) * h2
w_comb(1:nq,3) = w_comb(1:nq,3) + q(1:nq,nb+1) * h3
h1 = hh(nb-1,1)
h2 = hh(nb ,2)
x(1:nq) = x(1:nq) + q(1:nq,nb+2) * h1
y(1:nq) = y(1:nq) + q(1:nq,nb+2) * h2
w_comb(1:nq,1) = w_comb(1:nq,1) + q(1:nq,nb+2) * h1
w_comb(1:nq,2) = w_comb(1:nq,2) + q(1:nq,nb+2) * h2
h1 = hh(nb,1)
x(1:nq) = x(1:nq) + q(1:nq,nb+3) * h1
w_comb(1:nq,1) = w_comb(1:nq,1) + q(1:nq,nb+3) * h1
! Rank-1 update
tau1 = hh(1,1)
......@@ -178,36 +178,32 @@
tau3 = hh(1,3)
tau4 = hh(1,4)
x_orig = x
y_orig = y
z_orig = z
w_orig = w
! x_orig = x
! y_orig = y
! z_orig = z
! w_orig = w
h4m = 0.0
h4m(1,1) = tau1
x(1:nq) = x(1:nq) * h4m(1,1)
w_comb(1:nq,1) = w_comb(1:nq,1) * h4m(1,1)
h4m(2,1) = - tau2 * s_mat(1,2)
h4m(2,2) = tau2
y(1:nq) = x(1:nq) * h4m(2,1) + y(1:nq) * h4m(2,2)
w_comb(1:nq,2) = w_comb(1:nq,1) * h4m(2,1) + w_comb(1:nq,2) * h4m(2,2)
h4m(3,1) = - tau3 * s_mat(1,3)
h4m(3,2) = - tau3 * s_mat(2,3)
h4m(3,3) = tau3
z(1:nq) = x(1:nq) * h4m(3,1) + y(1:nq) * h4m(3,2) + z(1:nq) * h4m(3,3)
w_comb(1:nq,3) = w_comb(1:nq,1) * h4m(3,1) + w_comb(1:nq,2) * h4m(3,2) + w_comb(1:nq,3) * h4m(3,3)
h4m(4,1) = - tau4 * s_mat(1,4)
h4m(4,2) = - tau4 * s_mat(2,4)
h4m(4,3) = - tau4 * s_mat(3,4)
h4m(4,4) = tau4
w(1:nq) = x(1:nq) * h4m(4,1) + y(1:nq) * h4m(4,2) + z(1:nq) * h4m(4,3) + w(1:nq) * h4m(4,4)
w_comb(1:nq,4) = w_comb(1:nq,1) * h4m(4,1) + w_comb(1:nq,2) * h4m(4,2) + w_comb(1:nq,3) * h4m(4,3) + w_comb(1:nq,4) * h4m(4,4)
w_comb(:,1) = x
w_comb(:,2) = y
w_comb(:,3) = z
w_comb(:,4) = w
q(1:nq, 1:nb+3) = matmul(w_comb, h_mat) + q(1:nq, 1:nb+3)
......
Markdown is supported
0% or
You are about to add 0 people to the discussion. Proceed with caution.
Finish editing this message first!
Please register or to comment